HR Digital Transformation, Digital Work Culture, and Local Values: Evidence from Gorontalo University - Ismail, Silveny; Baruwadi, Mahludin; Paramata, Mohamad Rolli; Karundeng, Deby Rita (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Digital transformation in human resource management is increasingly essential for regional universities seeking to improve competitiveness and efficiency. This study examines how HR digital transformation affects employee performance, focusing on the mediating role of digital work culture rooted in local values. Using a sequential explanatory mixed-methods design, data were collected from 136 lecturers and administrative staff at Gorontalo University, Indonesia. The quantitative phase employed Structural Equation Modeling-Partial Least Squares (SEM-PLS), followed by thematic analysis of interviews with 10 key informants. The results indicate that HR digital transformation significantly affects employee performance, both directly (β = 0.61; p < 0.001) and indirectly through digital work culture as a partial mediating variable (β_indirect = 0.17; p < 0.01). Digital transformation also has a positive effect on digital work culture (β = 0.58; p < 0.001), and digital work culture positively influences employee performance (β = 0.29; p < 0.01). The coefficient of determination (R² = 0.73) shows that the model explains 73% of the variance in employee performance, with an adequate Goodness of Fit level (SRMR = 0.065). The qualitative findings reinforce the quantitative results by revealing the emergence of “digital kinship,” a form of collaborative digital solidarity rooted in the local value of mosidara (mutual respect and cooperation). This study offers new insights by integrating the Resource-Based View and Dynamic Capability Theory, showing that successful digital transformation relies not only on technology adoption but also on cultivating a digital work culture grounded in local wisdom and digital work ethics.